2007
DOI: 10.1080/15569520701555359
|View full text |Cite
|
Sign up to set email alerts
|

Does Irritation Potency Contribute to the Skin Sensitization Potency of Contact Allergens?

Abstract: Chemicals that possess the capacity to cause skin sensitization have long been recognized to be reactive (electrophilic) or at least the precursor of an electrophile. The chemical species (hapten) covalently bound to skin protein then forms the antigen to which the immune system responds, with sufficient exposure ultimately leading to skin sensitization. However, for this process to occur, many have also considered that in addition to haptenation of skin protein, secondary stimuli (danger signals) are also nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…4). Statistical analysis of a larger set of 55 substances using data from LLNA and GPMT was also not conclusive (Basketter et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…4). Statistical analysis of a larger set of 55 substances using data from LLNA and GPMT was also not conclusive (Basketter et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the irritant potency of a chemical has been shown in vivo and in vitro to be directly related to sensitization potency, and it has also been shown that skin irritation is related to the development and severity of allergic contact dermatitis 29, 30, 31, 32. In this study, we have shown that the inks vary considerably in their irritant potency, as illustrated by the broad range of EC50 values obtained after addition of inks to the culture medium of RHS (EC50 0.04% to EC50 not reached).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructed epidermal models (EE) using primary human keratinocytes are currently used to test whether a chemical has irritant/corrosive properties or not (Fentem et al, 1998;Liebsch et al, 2000;Spielmann et al, 2007). The initial protocol for the potency classification was based on the clinical observation that there is a clear role of irritancy in contact sensitization due to the irritant property of many allergens (Agner et al, 2002;Basketter et al, 2007;Bonneville et al, 2007;McLelland et al, 1991). Chemicals must cause sufficient local trauma to increase cutaneous cytokine production.…”
Section: Introductionmentioning
confidence: 99%